Observations on the Targumic Character of the Prologue of John - Borgen, Peder 1928-2023 (1970)
Recent analyses of the Prologue of John have to a large degree centred around two questions, (1) the question of poetic and prose forms of styles, and (2) the question of unity or disunity of thought, both within the Prologue itself and between the Prologue and the rest of the Gospel. Several scholars, such as R. Bultmann, E. Käsemann, R. Schnackenburg and R. E. Brown, have reached the conclusion that the Evangelist has used and partly reshaped and supplemented a hymn.1 This hyposthesis has drawn criticism from scholars who stress that this distinction between poetry and prose is impossible to maintain. Thus E. Haenchen and W. Eltester have characterized the style as hymnic prose.